NO SHOT IN THE DARK – FACTORS FOR A SUCCESSFUL IMPLEMENTATION OF COLLABORATIVE HOUSING PROJECTS - Höflehner, Thomas; Simic, Danko; Siebenbrunner, Anna (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
The aim of this paper is to detect factors for a successful implementation of collaborative housing projects based on experiences and lessons learned in various Styrian examples. Styria, as well as Austria, has a longstanding tradition in resident orientated housing policies and a well-established cooperative sector. To gain an insight into current chances, challenges and obstacles to participatory housing initiatives, three expert interviews were conducted. Subsequently, general factors of success were abstracted and discussed as the main findings of this paper. These factors should by no means be understood as a checklist for success. In fact, they can be used as a guideline or general required framework on the way towards successful collaborative housing projects.